RCMP Officers Posted to Nunavut Communities: Exploring the Policing and Private Life Challenges of Qallunaat Police in Inuit Nunangat - Hamel-Touchette, Sophie (Université d'Ottawa | University of Ottawa, 2025)
As a result of a signed agreement between the Government of Canada and Nunavut, the Royal Canadian Mounted Police (RCMP) is contracted to police Nunavut hamlets. This iteration of contracts began when the Territory was formed in 1999 and involves the recruitment of Regular Members from across Canada. To better understand the experiences of these Members, this thesis project engages with the literature on rural and remote policing, and explores the uniqueness of policing in Nunavut (Ruddell & Jones, 2018). Inspired by informal Member comments about the “harsh reality” of these posts, this project investigates accounts of everyday policing in several hamlets. Through a qualitative approach, specifically semi-structured interviews, and framed by Settler Colonialism theory and Bourdieu's theory on Habitus, this project applies “policing habitus” to understand the daily living and working conditions of police officers in Nunavut. The analysis shows that officers identify a number of obstacles in their “field” of work, including insufficient resources for the communities of Nunavut, a complex array of responsibilities and requests that fall outside of police duties and yet to them, the complexities of negotiating relationships in small hamlets, and the frustration of feeling as though they are a “band-aid” solution to deep and historical issues. The thesis concludes with a series of policy recommendations.
Keywords: Nunavut; Officers; RCMP; Inuit; Rural Policing; Northern Communities; Habitus; Field; Settler Colonialism; Colonization; Policing Habitus